COVID-19 preventive practices and associated factors among high school and preparatory school students in Dessie City, Ethiopia - Feleke, Alelgne; Gebrehiwot, Mesfin; Kloos, Helmut; Embrandiri, Asha; Daba, Chala; Hassen, Seada; Adane, Metadel (Frontiers in Public Health, 2022)
Background: As the COVID-19 pandemic continues to ravage the world, the most pretentious sector besides the economy is the education system. Ethiopia is not equipped with the infrastructure and facilities to provide online classes for students at all levels. Hence, all institutions were re-opened with mandatory infection prevention and control (IPC) protocols such as the use of face masks, physical distancing, shifts in classes, and routine hand washing practices with soap and water to restrict the spread of the virus. Nevertheless, there has been no monitoring and follow- up and there is no data on IPC compliance among school children in the country. The purpose of this study was to examine the preventive practices and their associated factors in COVID-19 among high and preparatory school students in Dessie City, Ethiopia. Methods: A cross-sectional study of five high schools and preparatory schools was carried out by using a pre-tested face-to-face applied structured questionnaire and direct observations from March 8 to March 20, 2021, in five high and preparatory schools in Dessie City. The sample size was proportionally allocated in each school based on the students' total number registered in the first academic semester, then stratified by grade level, and proportionally allocated to each grade and section. Finally, a simple random sampling method was used to select study participants. Variables with p-values < 0.25 in the bivariate logistic regression analysis were entered into the multivariate logistic regression model. Results: This study involved 422 students with a response rate of 98.8%. The level of good preventive practices was 43.7%. After adjusting for covariates, female, positive attitudes, received IPC training and clear accessible sharing of information and feedback with parents, students and teachers were identified as predictors of good precaution practices. Conclusion: The prevalence of good prevention practices for COVID-19 among students was relatively very low. Therefore, the Department of Health and Education of Dessie City and each school should implement environmental health programs and promote prevention practices in high schools and preparatory schools.